2013
DOI: 10.1590/s1806-83242013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1.23% APF gel applications on incipient carious lesions: a double-blind randomized clinical trial

Abstract: The aim of this double-blind randomized clinical trial was to evaluate the efficacy of 1.23% APF gel application on the arrest of active incipient carious lesions in children. Sixty 7-to 12-year-old children, with active incipient lesions were included in the study. Children were divided randomly into 2 groups: 1.23% APF gel and placebo gel applications. Each group received 8 weekly applications of treatment. The lesions were re-evaluated at the 4 th and 8 th appointments. Poisson regression analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
(29 reference statements)
1
21
0
7
Order By: Relevance
“…The study protocol was reviewed and approved by the ethics committee of Mashhad University of Medical Sciences and an informed consent document was taken from each patient’s parent/legal guardian after a brief explanation of the treatment process. The sample size for each group was calculated as n = 20, based on an alpha significance level of 0.05 and a beta of 0.2, according to the data obtained from a previous study (23). …”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was reviewed and approved by the ethics committee of Mashhad University of Medical Sciences and an informed consent document was taken from each patient’s parent/legal guardian after a brief explanation of the treatment process. The sample size for each group was calculated as n = 20, based on an alpha significance level of 0.05 and a beta of 0.2, according to the data obtained from a previous study (23). …”
Section: Methodsmentioning
confidence: 99%
“…Viewing a thick biofilm suggests increased caries risk, since its presence on this carious lesion is a strong indicator for its activity. Biofilm control is an effective way to interrupt the injury [22]. Hygiene guidance should be directed to individual needs, especially in areas with active caries lesions [23], and their remineralization will only be effective when there is a change of oral hygiene habits [24].…”
Section: Resultsmentioning
confidence: 99%
“…The most initial measure was public water fluoridation in the USA and Canada, which was subsequently adapted by other countries worldwide 26) . Currently, fluoride is widely used as a prophylactic agent for early dental caries, and it is extensively used in clinical settings as a form of preventive therapy on the basis of reports of its ability to prevent initial carious lesions via plaque removal, removal of demineralized enamel without exposing the tooth surface to cariogenic challenge, and promotion of enamel remineralization by minimizing mineral loss 3,6,27) . A low concentration of fluoride must remain on the enamel surface in the oral cavity, and good effects can be achieved if plaque, saliva, and oral soft tissues act as reservoirs and remain loosely bound to the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, caries prevention is important. In addition to regular tooth-brushing after meals, regular check-ups and preventive treatment using sealants and In particular, fluoride gel has been widely used in clinical settings because of the excellent costeffectiveness 5,6) . Some existing studies have reported that the rate of caries prevention by fluoride application varies between 20% and 30% [7][8][9][10] , whereas other randomized clinical trials have reported no differences between fluoride application and control groups 11) .…”
Section: Introductionmentioning
confidence: 99%